2017
DOI: 10.1099/jgv.0.000809
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-mediated haemagglutination of recent human influenza A(H3N2) viruses is determined by arginine 150 flanking the neuraminidase catalytic site

Abstract: Over the last decade, an increasing proportion of circulating human influenza A(H3N2) viruses exhibited haemagglutination activity that was sensitive to neuraminidase inhibitors. This change in haemagglutination as compared to older circulating A(H3N2) viruses prompted an investigation of the underlying molecular basis. Recent human influenza A(H3N2) viruses were found to agglutinate turkey erythrocytes in a manner that could be blocked with either oseltamivir or neuraminidase-specific antisera, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Mutations in the active site are primarily observed upon development of resistance against NA inhibitors (NAIs) [64][65][66][67]. As an exception, recent human H3N2 viruses that depend on NA rather than HA for hemagglutination were recently shown to carry HA proteins with very weak receptor-binding properties and NA with presumed low activity due to a mutation in the catalytic site [68]. NA-dependent hemagglutination could also be observed upon passaging of H3N2 viruses on MDCK cells [69].…”
Section: Glossarymentioning
confidence: 99%
“…Mutations in the active site are primarily observed upon development of resistance against NA inhibitors (NAIs) [64][65][66][67]. As an exception, recent human H3N2 viruses that depend on NA rather than HA for hemagglutination were recently shown to carry HA proteins with very weak receptor-binding properties and NA with presumed low activity due to a mutation in the catalytic site [68]. NA-dependent hemagglutination could also be observed upon passaging of H3N2 viruses on MDCK cells [69].…”
Section: Glossarymentioning
confidence: 99%
“…The last two points are important, since NA-based immunity, if robust enough, might have a significant impact on the transmission of the virus, which might increase the effectiveness of the influenza virus vaccine even in areas with low vaccine coverage. Finally, it has been reported that some of the currently circulating H3N2 viruses use their NA instead of their HA for attachment to cells ( 66 68 ). In this case, anti-NA antibodies might also have HI activity.…”
Section: What Do We Need To Know?mentioning
confidence: 99%
“…It was shown recently [ 9 ] that an H150R mutation in the NA of A/H3N2 viruses was responsible for the NA-mediated agglutination of turkey RBCs. This mutation became fixed in the majority of circulating viruses around 2008.…”
Section: Resultsmentioning
confidence: 99%